Direct and Indirect Modulation of T Cells by VEGF-A Counteracted by Anti-Angiogenic Treatment - Bourhis, Morgane; Palle, Juliette; Galy-Fauroux, Isabelle; Terme, Magali (Frontiers in Immunology, 2021)
Vascular endothelial growth factor A is known to play a central role in tumor angiogenesis. Several studies showed that VEGF-A is also an immunosuppressive factor. In tumor-bearing hosts, VEGF-A can modulate immune cells (DC, MDSC, TAM) to induce the accumulation of regulatory T-cells while simultaneously inhibiting T-cell functions. Furthermore, VEGFR2 expression on activated T-cells and FoxP3high regulatory T-cells also allow a direct effect of VEGF-A. Anti-angiogenic agents targeting VEGF-A/VEGFR contribute to limit tumor-induced immunosuppression. Based on interesting preclinical studies, many clinical trials have been conducted to investigate the efficacy of anti-VEGF-A/VEGFR treatments combined with immune checkpoint blockade leading to the approvement of these associations in different tumor locations. In this review, we focus on the impact of VEGF-A on immune cells especially regulatory and effector T-cells and different therapeutic strategies to restore an antitumor immunity.